Use of Ultrasonic Energy in Dyeing of Microfiber - Merdan, Nigar; Inanici, Yusuf (Asian Journal of Chemistry, 2011)
In recent years, dyeing kinetics in dyeing of polyamide microfiber become more important in recent years due to its use in textile industry and its functional features, with C.I. reactive yellow 39, C.I. reactive red 84 and C.I. reactive blue 69 was studied and conventional dyeing method and the method in which ultrasonic energy is used were compared from the point of view of dye uptake %, dyestuff amount, which moves away during washing, fixation %, significant rate, half-dyeing time, standard affinity and diffusion coefficient. Also, the samples, which had been dyed by using conventional and ultrasonic methods, were compared with washing, light, perspiration and rubbing fastness as well as the values of DE*, DL*, Da* and Db*, which were obtained from colourimetric measurements.